Introduction to Economic Criminal Law - Lamas Puccio, Luis (1987)
The text analyzes economic criminal law, highlighting both its controversial nature and its growing importance in the legal field. It explains that, unlike traditional crime, characterized by violence and tangible consequences, economic crimes -such as corporate fraud and abuse of power- are distinguished by their complexity, intangible nature and the frequent involvement of agents belonging to high socioeconomic strata, which makes their identification and adequate criminalization difficult. The author argues that this is due to the inadequacy of existing legal norms, cultural deficiencies that limit their understanding and a certain legislative laxity towards these crimes. He also states that conventional statistics do not reflect their real impact, underestimating the economic and social damage they cause. Consequently, he states that the absence of an updated legal framework that adequately addresses these transgressions aggravates the problem, recalling the urgent need to develop specific regulations that protect collective legal assets and respond effectively to these new forms of criminality, especially in an increasingly technological society.